2019
DOI: 10.1007/s42978-019-0010-y
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Dependent Modulation of Bone Metabolism and Bone Endocrine Function: New Findings and Therapeutic Perspectives

Abstract: Physical inactivity is the fourth leading cause of mortality worldwide; regardless of geographic location and income, it is a contributing risk factor to the other three causes. Physical activity is really a drug, a poly-pill; its "regular use" can reduce this risk throughout the activation of a plethora of responses in virtually all the body tissues. The beneficial effects of physical activity on cardiovascular function and hemodynamics are mainly mediated by skeletal muscle, adipose tissue and the immune sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 70 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…It is negatively regulated by acute exercise and training (endurance and resistance in overweight and obese men) [ 160 , 233 ]. Numbering among the antagonists of myostatin are follistatin (FST), follistatin-like 1 (FSTL1), and decorin [ 160 , 234 ].…”
Section: Direct and Indirect Effects Of Pth On Skeletal Muscle Masmentioning
confidence: 99%
“…It is negatively regulated by acute exercise and training (endurance and resistance in overweight and obese men) [ 160 , 233 ]. Numbering among the antagonists of myostatin are follistatin (FST), follistatin-like 1 (FSTL1), and decorin [ 160 , 234 ].…”
Section: Direct and Indirect Effects Of Pth On Skeletal Muscle Masmentioning
confidence: 99%
“…Research carried out in recent years has demonstrated that sclerostin is important for bone homeostasis 2 , 36 , and its expression in osteocytes has been found to be negatively regulated by mechanical loading 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Muscles and bones interact to maintain their structures and functions. Thus far, we have realized that muscles and bones can receive and secrete biochemical signals in a two-way manner, thereby affecting the metabolism of the two tissues and the entire body ( Lombardi, 2019 ; Gomarasca et al, 2020 ). These signals are coordinated by a set of cytokines and growth-like factors: muscle factors secreted by muscle cells and bone factors secreted by bone cells, both of which can exert autocrine, paracrine and endocrine functions to regulate muscle and bone metabolism.…”
Section: Bone-muscle Biochemical Crosstalkmentioning
confidence: 99%